The reactions of the governments of the Americas to the international crisis : an overview of policy measures up to 31 May 2009 (ECLAC [Santiago]CL, 2009)
Outlines measures which are aimed to restore confidence and unlock financial markets or to bolster weakened aggregate demand.
Keywords: ECONOMIC RECESSION